Enhancing Teachers' Scientific Writing Skills Through Community Service: A Case Study at SMK Negeri 1 Darul Kamal: Penguatan Keterampilan Penulisan Ilmiah Guru Melalui Pengabdian kepada Masyarakat: Studi Kasus di SMK Negeri 1 Darul Kamal - Melinda; Budi Arianto; Safrizal Razali; Yuwaldi Away; Nurmalia Zakaria (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The Community Service Program at SMK Negeri 1 Darul Kamal is designed to enhance the scientific writing skills of teachers, with the aim of improving the quality of publications and teaching materials. The program includes an initial socialization of its objectives, discussions to identify writing needs, as well as careful coordination and development of training modules. Conducted through interactive workshops, the training utilizes advanced technologies such as data analysis software and scientific reference management tools. Evaluation of the program through pre-test and post-test questionnaires demonstrated significant improvements in methodology understanding, writing habits, motivation for writing, and mastery of educational technology. Notable improvements were recorded with average scores for understanding research methodologies increasing from 2.9 to 4.4, and motivation for writing rising from 2.6 to 3.6. These results validate the success of the training in improving both the quality and efficiency of scientific writing among teachers. Based on these findings, it is recommended that similar training programs be extended to more educators across Indonesia to help raise educational standards and enhance teacher professionalism nationally. This initiative not only supports profession development but also aligns with national educational goals, thereby making a significant contribution to the academic community.